(untitled) (Bangladesh Journal of Medical Science, 2016)
Objective: There are many unknown safety for consumption in a compound of medicinal plants, one of them is polysaccharide peptide (PSP) of the extract of Ganoderma lucidum. Polysaccharide peptide (PSP) from Ganoderma lucidum mushroom extract is a bioactive substances found in the mushroom that is expected to be a drug that is safe for consumption. It is an antioxidant that has been used in the wider community as a chronic hepatopathic medicine, hypertension, and hyperglycemia. PSP cannot be circulated to the public before passing some toxicity tests to obtain information about its safety and to investigate the effect. There are many things that can be assessed from this toxicity test, some of them are lipid profile that includes (cholesterol, HDL, LDL, and TG) and blood profile (leukocytes, erythrocytes, and platelets). Materials and Methods: This study used experimental post test only control group design. The sample consisted of 80 Rattus norvegicus Wistar strain (40 males and 40 females) were divided into normal group, the group with the administration of a dose PSP 300, 600, 1200 mg/kg/hr) for 90 days. Parameters measured were lipid and hematological profile. Results and Discussion: The result of the analysis using ANOVA showed no significant effect on the administration of PSP on the level lipid and hematologic profile. The examination showed not significant at the lipid profile (cholesterol, TG, HDL, and LDL) and leukocytes. It is same as platelet and erythrocytes profile whereas there is only PCT, MCV, MCH, RBC, and RDW changed significantly, but still within normal limits. Conclusion: Administration Polysaccharide peptide in subchronic study mostly showed no significant effect on the levels of lipid profiles and hematology even though there is significant effect in some parameters but it still within the normal limit. Findings from this study suggest that Polysaccharide peptide of Ganoderma lucidum is safe and can be exploited in healthcare delivery systems. Bangladesh Journal of Medical Science Vol.15(3) 2016 p.409-415